Menelusuri Literatur-Historis Desa di Indonesia: Pola dari Pemukiman Seadanya menjadi Pemukiman Se-barunya - Nurkhalis Nurkhalis; Nodi Marefanda (Jurnal Community, 2016)
Rural settlements are the history of the origin for some people even nearly reached the total for the life of Indonesian citizens. So much can be known in naming various villages in Indonesia; gampong, kampung, nagari, and so on. The settlement will be an interesting story that was started from portion of the issue of welfare, livelihoods, even re-survival after a bit of social upheavals and natural disasters. This paper will explore further the conditions are at two moment; past and present. Although it is not representative of the overall condition of the countryside in Indonesia, the author hopes this article become a representation when discuss what, why and how are the rural. Keywords : history, village, settlements, rural settlements